2022
DOI: 10.1029/2021ef002448
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Stilling Projected to Continue in the Northern Hemisphere Mid‐Latitudes

Abstract: The near‐surface wind speed over land has declined in recent decades, a trend known as terrestrial stilling (TS). However, recent studies have indicated a reversal of the TS during the last decade, triggering renovated interest in the future wind speed changes. This study examines the TS over the Northern Hemisphere (NH) land areas and explores its future changes under Model Inter‐comparison Projection Phase 6 Shared Socioeconomic Pathways (SSP) scenarios. The results show that the NH mid‐latitude TS will like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…This expansion translates into more days with weather more akin to that of southern Europe. That agrees with a projected weakening of near-surface wind speed over land under anticipated high greenhouse warmings (Deng et al, 2022). This increase in summer days dominated by weaker meridional pressure gradients has also been reported in previous studies focusing on central Europe (Herrera-Lormendez et al, 2021) and in the prior generation of CMIP GCMs (Otero et al, 2018).…”
Section: Future Changes and Contribution Of Ct Frequenciessupporting
confidence: 90%
“…This expansion translates into more days with weather more akin to that of southern Europe. That agrees with a projected weakening of near-surface wind speed over land under anticipated high greenhouse warmings (Deng et al, 2022). This increase in summer days dominated by weaker meridional pressure gradients has also been reported in previous studies focusing on central Europe (Herrera-Lormendez et al, 2021) and in the prior generation of CMIP GCMs (Otero et al, 2018).…”
Section: Future Changes and Contribution Of Ct Frequenciessupporting
confidence: 90%
“…These factors were also discussed in other studies, e.g. Azorin-Molina et al (2018); Deng et al (2022); Minola et al (2022); Zha et al (2021). Deng et al (2022) also found that reversal of stilling was reproduced in a group of CMIP6 models, but only for the period of 2010 to 2030.…”
Section: Introductionsupporting
confidence: 59%
“…Azorin-Molina et al (2018); Deng et al (2022); Minola et al (2022); Zha et al (2021). Deng et al (2022) also found that reversal of stilling was reproduced in a group of CMIP6 models, but only for the period of 2010 to 2030. However, Dunn et al (2022) unveiled that this reversal of global stilling was overestimated due to a change in how calm winds were encoded (as missing if < 1 m.s -1 , before if < 0.5 m.s -1 ) in part of the global station network databases since 2013.…”
Section: Introductionmentioning
confidence: 87%
“…The three main decadal oscillations having the largest impact on wind speed variation are the Tropical Northern Atlantic Index (TNA), the Pacific Decadal Oscillation and the North Atlantic Oscillation. These factors were also discussed in other studies, for example, Azorin-Molina et al (2018), Deng et al (2022), Minola et al (2022), andZha et al (2021). Deng et al (2022) also found that reversal of stilling was reproduced in a group of CMIP6 models, but only for the period of -2030.…”
mentioning
confidence: 58%
“…Deng et al (2021) suggested that the stilling in the northern hemisphere could be explained by multiple causes including changes in large scale circulation, vegetation and land-use, and greenhouse gas concentration increase. The stilling is likely to be preserved and closely associated with warming intensity till the end of century by CMIP6 simulations, i.e., the higher warming scenario, the larger the decline in SWS (Deng et al, 2022) A review of worldwide terrestrial stilling and its potential causes can be found in McVicar et al (2012) and Wu et al (2018).…”
mentioning
confidence: 99%